A hidden ally in laparoscopic cholecystectomy: quadratus lumborum block and the quest for pain-free recovery - Chooklin, Serge; Chuklin, Serhii (Frontiers in Surgery, 2025)
Laparoscopic cholecystectomy (LC) is a minimally invasive procedure; however, it is frequently associated with considerable postoperative pain, which in some cases may progress to chronic pain. The underlying mechanisms are multifactorial and include trocar insertion, wound trauma, surgical manipulation of the gallbladder and adjacent organs, carbon dioxide insufflation, diaphragmatic irritation with referred shoulder pain, local inflammation, and, occasionally, nerve injury (0.02%–1%). Effective pain management is crucial not only for patient comfort but also for minimizing postoperative complications and facilitating faster recovery. The quadratus lumborum block (QLB) is an ultrasound-guided regional anesthetic technique that has gained increasing recognition as a component of multimodal analgesia for LC. By depositing local anesthetic adjacent to the quadratus lumborum muscle, the QLB can interrupt thoracolumbar nerve transmission, thereby providing both somatic and visceral analgesia. Across randomized and prospective studies, QLB is often associated with lower early postoperative pain scores, delayed time to rescue analgesia, and reduced opioid use; however, several trials report no significant differences or equivalence vs. other regional techniques (e.g., TAPB, ESPB) within multimodal analgesia. These mixed results likely reflect heterogeneity in QLB approach (posterior, lateral, anterior), injectate volume/concentration, comparators, and outcome definitions. The extent of analgesic coverage depends on the type of QLB performed, the administered volume of anesthetic, and patient-specific anatomical variations. Accordingly, the objective of this narrative review is to synthesize adult clinical evidence on QLB for LC, compare approach-specific analgesic and opioid-sparing effectiveness with alternative regional techniques and standard care, evaluate safety. This review summarizes current evidence on the use of QLB in LC, with a focus on its mechanisms, techniques, clinical efficacy, and limitations. Although QLB appears promising as an effective opioid-sparing strategy, given the heterogeneity and risk-of-bias concerns across studies, conclusions are moderated, and high-quality, standardized RCTs are needed.